1996
DOI: 10.1007/s002849900063
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Chemotaxis Mutants of Chlamydomonas reinhardtii

Abstract: Zoospores of Chlamydomonas reinhardtii exhibit chemotaxis towards maltose, sucrose, xylose, mannitol, and ammonium. Ten independent mutants defective in chemotaxis towards sugars have been isolated. These mutants form five phenotypic classes. Genetic analysis of two mutant strains defective in chemotaxis to maltose (CHE1, CHE3) and two mutant strains defective in chemotaxis to sucrose (CHE2, CHE4) indicated that the defect in them depended on single nuclear recessive mutant alleles. Mutations mal1, mal2, suc1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…2F) might be a reflection of the functioning of multiple pathways with different light-intensity dependencies. Such multiple pathways for motility control might be important not only for producing phototactic behavior but for integrating various signals from external conditions, including chemicals (Hirschberg and Rogers, 1978;Ermilova et al, 1996), gravity (Bean, 1977;Yoshimura et al, 2003) and light.…”
Section: +mentioning
confidence: 99%
“…2F) might be a reflection of the functioning of multiple pathways with different light-intensity dependencies. Such multiple pathways for motility control might be important not only for producing phototactic behavior but for integrating various signals from external conditions, including chemicals (Hirschberg and Rogers, 1978;Ermilova et al, 1996), gravity (Bean, 1977;Yoshimura et al, 2003) and light.…”
Section: +mentioning
confidence: 99%
“…This contrasts with the strong chemoresponse of A. gubernaculifera to acetate. Asterphomene gubernaculifera was not attracted to sugars as was C. reinhardtii (Ermilova et al 1993, 1996) nor to amino acids as were D. tertiolecta (Sjoblad et al 1978b) and D. salina (Kohidai et al 1996), except that phenylalanine attracted both A. gubernaculifera and D. tertiolecta (Sjoblad et al 1978b).…”
Section: Discussionmentioning
confidence: 98%
“…We used several different methods to demonstrate chemoattraction of A. gubernaculifera by acetate. Within the chlorophytes, Chlamydomonas and the related alga Dunaliella have been reported to be chemoattracted by organic (Sjoblad et al 1978b, Hirschberg and Rodgers 1978, Ermilova et al 1993, 1996, Kohidai et al 1996) and inorganic (Hirschberg and Rodgers 1978, Sjoblad et al 1978b, Sjoblad and Frederikse 1981, Byrne et al 1992) molecules. In general, these studies have shown a consistent attraction of these algae to ammonium ions (Sjoblad et al 1978a, Hirschberg and Rodgers 1978, Sjoblad and Frederikse 1981, Byrne et al 1992) but very little consistency in the response to organic attractants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation